Comparison of videolaryngoscopy and direct laryngoscopy by German paramedics during out-of-hospital cardiopulmonary resuscitation; an observational prospective study - Joachim Risse; Christian Volberg; Thomas Kratz; Birgit Plöger; Andreas Jerrentrup; Dirk Pabst; Clemens Kill (BMC Emergency Medicine, 2020)
Abstract Background Videolaryngoscopy (VL) has become a popular method of intubation (ETI). Although VL may facilitate ETI in less-experienced rescuers there are limited data available concerning ETI performed by paramedics during CPR. The goal was to evaluate the impact VL compared with DL on intubation success and glottic view during CPR performed by German paramedics. We investigated in an observational prospective study the superiority of VL by paramedics during CPR compared with direct laryngoscopy (DL). Methods In a single Emergency Medical Service (EMS) in Germany with in total 32 ambulances paramedics underwent an initial instruction from in endotracheal intubation (ETI) with GlideScope® (GVL) during resuscitation. The primary endpoint was good visibility of the glottis (Cormack-Lehane grading 1/2), and the secondary endpoint was successful intubation comparing GVL and DL. Results In total n = 97 patients were included, n = 69 with DL (n = 85 intubation attempts) and n = 28 VL (n = 37 intubation attempts). Videolaryngoscopy resulted in a significantly improved visualization of the larynx compared with DL. In the group using GVL, 82% rated visualization of the glottis as CL 1&2 versus 55% in the DL group (p = 0.02). Despite better visualization of the larynx, there was no statistically significant difference in successful ETI between GVL and DL (GVL 75% vs. DL 68.1%, p = 0.63). Conclusions We found no difference in Overall and First Pass Success (FPS) between GVL and DL during CPR by German paramedics despite better glottic visualization with GVL. Therefore, we conclude that education in VL should also focus on insertion of the endotracheal tube, considering the different procedures of GVL. Trial registration German Clinical Trial Register DRKS00020976 , 27. February 2020 retrospectively registered.